THE RELATIONSHIP OF HUSBAND COACHES WITH REDUCTION OF PAIN IN THE PROCESS LABOR IN CIOMAS PUSKESMAS BOGOR DISTRICT, 2019: HUBUNGAN PENDAMPING SUAMI DENGAN PENGURANGAN RASA NYERI PADA PROSES PERSALINAN DI PUSKESMAS CIOMAS KABUPATEN BOGOR TAHUN 2019 - Elpinaria Elpinaria Girsang (Wijaya Husada, 2019)
Husband's companion is encouragement or motivation, to provide assistance and support to the mother during labor, the husband is the first and foremost person in giving encouragement to the wife before the other party gives encouragement, support and attention of a husband to a pregnant wife that will have an impact reduction of pain during labor in Ciomas Health Center, Bogor Regency. The factors that influence the reduction in labor pain include presenting (Husband), positioning, touch and massase, massage, artificial heat, immersion in water, breathing and music. This aims to identify Reduction of Pain in Husband's Companion in Ciomas Health Center, Bogor Regency in 2018. The purpose of this study was to find out the relationship between husband's companion and the reduction of pain in labor in Ciomas Puskesmas, Bogor Regency in 2018. This type of research is an analytical survey with a cross sectional approach. The method of sampling in this study uses total sampling technique with a sample of 30 respondents, Status data for reducing the patient's pain is obtained by observing The results of bivariate analysis using the chi-square test The proportion of respondents with the results of pain reduction when accompanied in labor more moderate pain than severe pain and very severe pain (53.3% 36.7% and 10.0% with ρ = 0.004; ρ <0.05), So Ho was rejected with Ha accepted which means there is a relationship between husband's companion and a reduction in pain Based on the conclusions of the research results, there is a suggestion for the husband's husband to always accompany him during the labor process so that he can reduce the pain in the labor process